b - Masuno, Shunmyo (UK : Michael Joseph, 2022)
Put yourself at ease with this highly practical, internationally bestselling guide to reducing anxiety and living worry free by the renowned Zen Buddhist author of ZEN- The Art of Simple Living. The highly anticipated follow-up to Zen- The Art of Simple Living, Shunmyo Masuno has written a practical guide that is not only an introduction to the Zen lifestyle, but a focussed, highly practical book on how to solve the pain of worry and stress. The book contains 48 lessons in succinct chapters that cover subjects like- how to stay in the present, how to stop comparing yourself to others, how to stay calm in stressful situations and how to take action now. This book will put readers at ease with highly practical knowledge and teachings from the author; it will reduce readers' anxiety and it will be a tool for living worry free"